PERANAN CYBER LAW DALAM PENANGANAN TINDAK PIDANA DI INDONESIA - Zainudin Hasan; M Rafi Alfath, Ahmad Mahardika, Rizki Rizaldi, Wafi Rizqullah H (Jurnal Komunikasi, 2024)
The use of an internet connection is not something new nowadays, everyone can access the internet wherever, whenever, wherever they need or want. Considering that internet use has negative impacts, such as cyber crime, when there is cyber crime, then we know that we need cyber law. Technological advances and their applications always have various implications, both for order of social life, for the development of the business world, for the development of values Morals, Ethics and Law. Through multimedia technology, this type of telecommunications has become very developed, not only covering basic telecommunications, but also other value-added technologies. Internet penetration is so large that if it is not used wisely then will give birth to crime in cyberspace or what is termed cybercrime or cyber crime which is a further development of computer crime. The research method uses a normative juridical approach, namely by examining laws and positive legal policies in Indonesia and then collecting data through library research. The data analysis used is qualitative juridical